2023
DOI: 10.1002/jcop.23019
|View full text |Cite
|
Sign up to set email alerts
|

Do program practices matter for mentors?: How implementation of empirically supported program practices is associated with youth mentoring relationship quality

Abstract: This study investigates how the implementation of program‐level practices by formal youth mentoring programs is associated with the quality of youth mentoring relationships as contexts for youth development and also examines whether this connection is mediated by the mentor‐staff working alliance. Using data from mentors (n = 542) participating in multiple programs (n = 55), multilevel path models examined hypothesized direct and mediated effects. Parallel analyses were conducted with assessments of program pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…Tailored supervision may support mentors to embrace challenges and manage expectations typical with early periods of the mentoring relationship. Taken together, the findings align with prior research on ongoing support and training in mentor program experience (Keller et al, 2020; 2023; McQuillin & Lyons, 2021). Furthermore, the findings are consistent with evidence from other intergenerational programs indicating program facilitation may influence the effect of program participation on adult participants' socioemotional benefits (e.g., self‐worth; McBride et al, 2012; Tang et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Tailored supervision may support mentors to embrace challenges and manage expectations typical with early periods of the mentoring relationship. Taken together, the findings align with prior research on ongoing support and training in mentor program experience (Keller et al, 2020; 2023; McQuillin & Lyons, 2021). Furthermore, the findings are consistent with evidence from other intergenerational programs indicating program facilitation may influence the effect of program participation on adult participants' socioemotional benefits (e.g., self‐worth; McBride et al, 2012; Tang et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Results align with previous research highlighting the importance of support from mentoring staff and program infrastructure, wherein a greater degree of program contact has been found to be associated with more positive mentor volunteer experiences (Keller et al, 2020) and reduced chance of premature match closure (McQuillin & Lyons, 2021). Furthermore, positive working alliances between mentors and program staff are associated with higher levels of mentor satisfaction and commitment in the mentoring relationship and more positive interactions between mentors and youth (Keller et al, 2023). The findings of this study contribute to this body of work by suggesting how different elements of support might be useful for mentors depending on the longevity of the match.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific program aspects are highly individualized and can vary largely from program to program (Lyons & McQuillin, 2021), mentoring research provides general guidelines on program practices (Garringer et al, 2015). Studies show that the use of research‐evidenced program practices is associated with high‐quality mentoring relationships and outcomes (Keller et al, 2023; Stelter et al, 2023). In the following, we provide examples of such research‐evidenced practices in the areas of program design, participant preparation, and implementation of mentoring programs.…”
Section: Planning and Implementing Effective Mentoring Programsmentioning
confidence: 99%
“…Furthermore, staff support and emphasis on adherence to program practices and suggested mentoring activities predicted more favorable mentoring outcomes (Keller & DuBois, 2021). The critical role of program support has received increasing attention in recent years (Karcher et al, 2023; Keller et al, 2023; Spencer et al, 2023). For instance, Karcher et al (2023) explored the effects of program staff support on youth mentoring outcomes in a structural equation model and found that program support impacted match length directly and indirectly via youth‐centeredness, goal‐oriented mentoring, and perceived match closeness.…”
Section: Planning and Implementing Effective Mentoring Programsmentioning
confidence: 99%
See 1 more Smart Citation